Multicarrier CDMA systems using time-domain and frequency-domain spreading codes. - You, C.W (IEEE Transactions on communications)
For wideband code-division multiple-access systems, the paper introduces a multicarrier modulation scheme that performs the spreading simultaneously in the time and frequency domains. This scheme attains higher flexibility and spectrum efficiency because system parameters can be selected at will. The performance is compared with that of a single carrier RAKE system by calculating the probability of error over a frequency-selective Rayleigh fading channel. The proposed scheme outperforms the single carrier RAKE system if the system parameters are selected properly for given conditions, such as bandwidth and delay spread.